3/x-2=1/x-1+7/(x+1)(x-2)

Simple and best practice solution for 3/x-2=1/x-1+7/(x+1)(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3/x-2=1/x-1+7/(x+1)(x-2) equation:



3/x-2=1/x-1+7/(x+1)(x-2)
We move all terms to the left:
3/x-2-(1/x-1+7/(x+1)(x-2))=0
We can not solve this equation

See similar equations:

| 4/3=(2/3)d | | 3(2x+5)=5(x+6) | | 3m+8(1)/(4)=9 | | (1)/(5)c-13=-23 | | c/4.6=1.5 | | 6z+(-2-7)z=1 | | (4x+3)+(3x+2)=0 | | w^2=18 | | (x-2)(x-3)=(x-4)(x+9) | | (w)/(-2.1)+18=-12 | | 7(10a+3)=70a+ | | (x-8)^2-2x=7 | | (5x-1)×(2×+2)=68 | | 0.03(56+2)=0.15(t+2)-0.24 | | 3+3(2x+1)=4x-6 | | 1/2+3/4=n+3/4 | | 3(y+2)=-6 | | 3y(y+2)=-6 | | 476=14+7/8x | | 6e-8-2e=-16 | | (x-9)(x-1)=12 | | Y=25+8(x) | | .18(y-7)+0.14y=0.04y-2.1 | | 3/8(p-8)+1/2p=(p-6) | | -12n-19=49 | | 2/(x-1)+5=17/(x-1) | | (x-8)(X+4)=(x-4)(x-3) | | 2x(x+3)=32 | | 8(2x-6)=12 | | 4x^2+13x-4x^2=3 | | 4K=12+2z | | -x)+x=22+x |

Equations solver categories